Spectrum of HIV-associated infectious diseases: A case series through the eyes of the histopathologist - Reena Mohanlal; Denasha L. Reddy (AOSIS, 2020)
Background: Human immunodeficiency virus (HIV) infection increases the risk of infection by a host of other opportunistic pathogens. The clinical presentations of these co-infections in immunocompromised patients are often atypical; therefore diagnosis is delayed in the absence of investigations such as tissue biopsy. Infection may involve sites that are difficult to access for biopsy and, as a consequence, there is limited diagnostic tissue available for analysis. The histopathologist, aided by ancillary tests, is relied upon to make a timeous and accurate diagnosis. Objectives: To illustrate key histological features of HIV-associated infectious diseases encountered in a histopathology laboratory and to highlight, with the aid of literature, the relevance of histopathology in diagnosis. Method: A retrospective descriptive case series of biopsies histologically diagnosed with HIV-associated infectious diseases over four years (2015-2019) was performed at the Chris Hani Baragwanath Academic Hospital National Health Laboratory Services Histopathology department. These cases have been photographed to illustrate microscopic aspects and will be accompanied by a literature review of opportunistic infections in the context of HIV infection. Results: This article highlights aspects of fungal, parasitic, viral and selected bacterial infections of people living with HIV for whom the histopathological examination of tissue was an essential component of the clinical diagnosis. Histological features are noted on routine slides and accompanied by diagnostic features revealed with histochemical and immunohistochemical stains. Conclusion: Medical practitioners working in areas of high HIV endemicity should be familiar with the variety of infectious diseases that are encountered and with the diagnostic importance of the histopathologist in clinical management.